2017
DOI: 10.1038/s41598-017-12672-1
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 Hemichannels Regulate the Expression of Wound Healing-Associated Genes in Human Gingival Fibroblasts

Abstract: Connexin 43 (Cx43) is the most ubiquitous connexin in various cells, and presents as hemichannels (HCs) and gap junctions (GJs) on the cell membrane. We have recently shown that Cx43 abundance was strongly reduced in fibroblasts of human gingival wounds, and blocking Cx43 function in cultured human gingival fibroblasts (GFBLs) strongly regulated the expression of wound healing-related genes. However, it is not known whether these responses involved Cx43 HCs or GJs. Here we show that Cx43 assembled into distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 79 publications
10
46
0
Order By: Relevance
“…After stimulation, AS HBFs exhibited different expression patterns of some proteins compared to NA HBFs. The most important and notable differences are amplified levels of α-SMA and connexin (Cx) 43 (protein involved in the intercellular transfer of small metabolites and ions via hexameric channels termed gap junctions) [ 236 , 237 ] in response to TGF-β administration in AS HBFs compared to NA HBFs (Fig. 1 —upregulation of α-SMA and Cx43) [ 46 , 223 , 234 , 238 ].…”
Section: Fibroblast Featuresmentioning
confidence: 99%
“…After stimulation, AS HBFs exhibited different expression patterns of some proteins compared to NA HBFs. The most important and notable differences are amplified levels of α-SMA and connexin (Cx) 43 (protein involved in the intercellular transfer of small metabolites and ions via hexameric channels termed gap junctions) [ 236 , 237 ] in response to TGF-β administration in AS HBFs compared to NA HBFs (Fig. 1 —upregulation of α-SMA and Cx43) [ 46 , 223 , 234 , 238 ].…”
Section: Fibroblast Featuresmentioning
confidence: 99%
“…Moreover, in our SL/DT assay protocol, the cells are washed with CaMg-PBS prior the loading of dyes dissolved also in CaMg-PBS, which should inhibit hemichannel activity. It has been demonstrated that the same in vitro model can be used for evaluation of both hemichannel activity by dye uptake assay, and GJIC by SL-DT assay [42][43][44] . Interestingly, some chemicals can regulate hemichannels and gap junction channels differently.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using Gap27 have also shown that this peptide is effective in improving rabbit corneal wound healing [ 39 ] and in primary human gingival fibroblasts, isolated from donors aged 26–48 years of age [ 29 ]. A further peptide TAT-Gap19, has also recently been reported to enhance scrape wound closure of human gingival fibroblasts [ 40 ]. TAT-Gap19, targeted to the intracellular loop of Cx43, was designed as a cell permeant peptide and has been extensively used to characterise interactions between the intracellular loop of Cx43 and the carboxy terminal tail [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This re-enforces our previous findings where irradiated juvenile fibroblasts were used and Gap27 effectively enhanced wound closure [ 22 ]. Hence in JFF cells and keratinocytes proliferation factors are not involved in the enhanced cell migration response, suggesting hemichannel signalling plays an important role in co-ordinating cellular responses [ 30 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation